Barriers to oral care: a cross-sectional analysis of the Canadian longitudinal study on aging (CLSA) - Vanessa De Rubeis; Ying Jiang; Margaret de Groh; Lisette Dufour; Annie Bronsard; Howard Morrison; Carol W. Bassim (BMC Oral Health, 2023)
Abstract Background Oral health plays a role in overall health, indicating the need to identify barriers to accessing oral care. The objective of this study was to identify barriers to accessing oral health care and examine the association between socioeconomic, psychosocial, and physical measures with access to oral health care among older Canadians. Methods A cross-sectional study was conducted using data from the Canadian Longitudinal Study on Aging (CLSA) follow-up 1 survey to analyze dental insurance and last oral health care visit. Logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for the association between socioeconomic, psychosocial, and physical measures with access to oral care, measured by dental insurance and last oral health visit. Results Among the 44,011 adults included in the study, 40% reported not having dental insurance while 15% had not visited an oral health professional in the previous 12 months. Several factors were identified as barriers to accessing oral health care including, no dental insurance, low household income, rural residence, and having no natural teeth. People with an annual income of <$50,000 were four times more likely to not have dental insurance (adjusted OR: 4.09; 95% CI: 3.80–4.39) and three times more likely to report not visiting an oral health professional in the previous 12 months (adjusted OR: 3.07; 95% CI: 2.74–3.44) compared to those with annual income greater than $100,000. Conclusions Identifying barriers to oral health care is important when developing public health strategies to improve access, however, further research is needed to identify the mechanisms as to why these barriers exist.